MIR222HG attenuates macrophage M2 polarization and allergic inflammation in allergic rhinitis by targeting the miR146a-5p/TRAF6/NF-κB axis - Wen, Silu; Li, Fen; Tang, Yulei; Dong, Lin; He, Yan; Deng, Yuqin; Tao, Zezhang (Frontiers in Immunology, 2023)
Although M2 macrophages are involved in the orchestration of type 2 inflammation in allergic diseases, the mechanisms underlying non-coding RNA (ncRNA)-mediated macrophage polarization in allergic rhinitis (AR) have not been systematically understood. Here, we identified long non-coding RNA (lncRNA) MIR222HG as a key regulator of macrophage polarization and revealed its role in AR. Consistent with our bioinformatic analysis of GSE165934 dataset derived from the Gene Expression Omnibus (GEO) database, lncRNA-MIR222HG and murine mir222hg were downregulated in our clinical samples and animal models of AR, respectively. Mir222hg was upregulated in M1 macrophages and downregulated in M2 macrophages. The allergen-ovalbumin facilitated polarization of RAW264.7 cells to the M2 phenotype, accompanied by the downregulation of mir222hg expression in a dose-dependent manner. Mir222hg facilitates macrophage M1 polarization and reverses M2 polarization caused by ovalbumin. Furthermore, mir222hg attenuates macrophage M2 polarization and allergic inflammation in the AR mouse model. Mechanistically, a series of gain- and loss-of-function experiments and rescue experiments were performed to verify the role of mir222hg as a ceRNA sponge that adsorbed miR146a-5p, upregulated Traf6, and activated the IKK/IκB/P65 pathway. Collectively, the data highlight the remarkable role of MIR222HG in the modulation of macrophage polarization and allergic inflammation, as well as its potential role as a novel AR biomarker or therapeutic target.